Cervical Laminoplasty Versus Posterior Laminectomy and Fusion: Trends in Utilization and Evaluation of Complication and Revision Surgery Rates. Issue 17 (1st September 2022) - McDonald, Christopher L.; Hershman, Stuart H.; Hogan, William; Alsoof, Daniel; DiSilvestro, Kevin J.; Zhang, Andrew S.; Kuris, Eren O.; Daniels, Alan H.
Abstract : Introduction: Cervical laminoplasty (LP) and laminectomy with fusion (LF) are common operations used to treat cervical spondylotic myelopathy. Conflicting data exist regarding which operation provides superior patient outcomes while minimizing the risk of complications. This study evaluates the trends of LP compared with LF over the past decade in patients with cervical myelopathy and examines long-term revision rates and complications between the two procedures. Methods: Patients aged 18 years or older who underwent LP or LF for cervical myelopathy from 2010 to 2019 were identified in the PearlDiver Mariner Database. Patients were grouped independently (LP versus fusion) and assessed for association with common medical and surgical complications. The primary outcome was the incidence of LP versus LF for cervical myelopathy over time. Secondary outcomes were revision rates up to 5 years postoperatively and the development of complications attributable to either surgery. Results: In total, 1, 420 patients underwent LP and 10, 440 patients underwent LF. Rates of LP (10.5% to 13.7%) and LF (86.3% to 89.5%) remained stable, although the number of procedures nearly doubled from 865 in 2010 to 1, 525 in 2019. On matched analysis, LP exhibited lower rates of wound complications, surgical site infections, spinal cord injury, dysphagia, cervical kyphosis, limb paralysis, incision and drainage/exploration, implant removal, respiratory failure, renal failure, and sepsis. Revision rates for both procedures at were not different at any time point. Conclusion: From 2010 to 2019, rates of LP have not increased and represent less than 15% of posterior-based myelopathy operations. Up to 5 years of follow-up, there were no differences in revision rates for LP compared with LF; however, LP was associated with fewer postoperative complications than LF. Level of Evidence: Level III retrospective cohort study